A STUDY OF MARKERS OF ALLERGY AMONG PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Bokhari, S.N.H.; Zafar, M.H. (Journal of Ayub Medical College Abbottabad, 1990)
23 patients with established Chronic Obstructive Pulmonary Disease (COPD), age range 25- 85 years, were randomly selected; this included 16 smokers and 7 ex-smokers. Another 23 patients who were non-smoker and non-COPD were selected as control group. Mean total leucocyte count (TLC) in smokers was 10.26 x 109/L, in ex-smokers 8.57, and in control group 8.06 and mean eosinophil count was 0.14, 0.12, 0.02 respectively. The percentage of prevalence of history of allergy in smokers was 25, cx- smokers 28.5 and control 13, and positive skin prick test was 56.3, 14.3 and 13 respectively. Among COPD prevalence of allergy to house-dust (39%), feathers (30.4%), straw dust (21.7%), cow-hair (21.7%), sheep wool (21.7) and tree pollens (21.7%) was relatively higher than other allergens. Eosinophil count and prevalence of skin allergic test is higher in patients with Chronic Obstructive Pulmonary Disease, who are active smokers as compared to ex-smokers. This is not related to the presence of history of allergy.